Whole-exome sequencing and bioinformatics analysis of a case of non-alpha-fetoprotein-elevated lung hepatoid adenocarcinoma - Yao, Yao; Guan, Xiaojiao; Bao, Guangyao; Liang, Jie; Li, Tian; Zhong, Xinwen (Frontiers in Pharmacology, 2022)
Hepatoid adenocarcinoma of the lung (HAL) is an exceptionally rare malignant tumor with prominent hepatocellular carcinoma (HCC)-like characteristics in organs or tissues outside the liver, while there is no tumor in the liver. Most HAL cases have various degrees of serum alpha-fetoprotein (AFP) levels and exhibit a similar origin and clonal evolution process to HCC. We studied a case of HAL without elevating the AFP level by performing whole-exome sequencing (WES) and bioinformatics analyses after surgical resection. Our results showed mutations in two driver genes, NLRP3 and PBX1, and we identified HNRNPR, TP73, CFAP57, COL11A1, RUSC1, SLC6A9, DISC1, NBPF26, and OR10K1 as potential driver mutation genes in HAL. In addition, 76 significantly mutated genes (SMG) were identified after the statistical test of each mutation type on genes.